Inactivation of the Mouse L-Proline Transporter PROT Alters Glutamatergic Synapse Biochemistry and Perturbs Behaviors Required to Respond to Environmental Changes - Schulz, Daniel; Morschel, Julia; Schuster, Stefanie; Eulenburg, Volker; Gomeza, Jesús (Frontiers in Molecular Neuroscience, 2018)
The endogenous neutral amino acid L-proline exhibits a variety of physiological and behavioral actions in the nervous system, highlighting the importance of accurately regulating its extracellular abundance. The L-proline transporter PROT (Slc6A7) is believed to control the spatial and temporal distribution of L-proline at glutamatergic synapses by rapid uptake of this amino acid into presynaptic terminals. Despite the importance of members of the Slc6 transporter family regulating neurotransmitter signaling and homeostasis in brain, evidence that PROT dysfunction supports risk for mental illness is lacking. Here we report the disruption of the PROT gene by homologous recombination. Mice defective in PROT displayed altered expression of glutamate transmission-related synaptic proteins in cortex and thalamus. PROT deficiency perturbed mouse behavior, exhibiting reduced locomotor activity, decreased approach motivation and impaired memory extinction. Thus, our study demonstrates that PROT regulates behaviors that are needed to respond to environmental changes in vivo and suggests that PROT dysfunctions might contribute to mental disorders showing altered response choice following task contingency changes.